2017
DOI: 10.21897/rmvz.1028
|View full text |Cite
|
Sign up to set email alerts
|

Variación génica intrapoblacional del caracol gigante africano (Achatina fulica) en el Valle del Cauca

Abstract: Objective. To evaluate the intrapopulation genetic variation of A. fulica in the Valle del Cauca. Materials and methods. Ten microsatellite loci from specimens collected at eight municipalities in the Valle del Cauca Department were amplified. Allelic frequencies and descriptors of intrapopulation genetic diversity were estimated. Bayesian analysis was used to estimate the number of groups present in the study area. Results. Two groups were identified in the Valle del Cauca (p > 50%): one group comprised indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…These authors observed a low or almost no genetic variability in most populations of the freshwater snail Pseudosuccinea columella (Say, 1817), with the detection of a single "World Invader" genotype. Patiño-Montoya & Giraldo (2017) has observed similar results to the giant African terrestrial snail Achatina fulica Bowdich, 1822, that presented low genetic diversity compared to populations in its natural distribution in Africa, due to a founding effect occurring in each introduction event and the bottlenecks occurring after the establishment and acclimatization to the conditions of the new habitat.…”
Section: Discussionmentioning
confidence: 54%
“…These authors observed a low or almost no genetic variability in most populations of the freshwater snail Pseudosuccinea columella (Say, 1817), with the detection of a single "World Invader" genotype. Patiño-Montoya & Giraldo (2017) has observed similar results to the giant African terrestrial snail Achatina fulica Bowdich, 1822, that presented low genetic diversity compared to populations in its natural distribution in Africa, due to a founding effect occurring in each introduction event and the bottlenecks occurring after the establishment and acclimatization to the conditions of the new habitat.…”
Section: Discussionmentioning
confidence: 54%
“…Debido a la naturaleza invasora del caracol gigante africano, es probable que al departamento del Valle del Cauca estén ingresando individuos de diferentes lugares, en diferentes temporadas e incluso con diferente intensidad (Fontanilla et al, 2014;Patiño-Montoya y Giraldo, 2017). Lo anterior, sumado al control diferencial sobre clases específicas de tamaño de la población (adultos) como consecuencia de las acciones de control implementada por la autoridad ambiental, explicaría la constante movilización de los individuos dentro de la población que se encontró en el análisis discriminante.…”
Section: Discussionunclassified
“…El caracol gigante africano (Achatina fulica) es considerado una de las 100 plagas más peligrosas a nivel mundial por la Unión Internacional para la Conservación de la Naturaleza (UICN) debido a la alta proliferación, polifagia y simpatía por parte del ser humano (Patiño-Montoya y Giraldo, 2017). La invasión de esta especie puede generar consecuencias devastadoras en el medio ambiente, como lo es el desplazamiento de especies nativas, ya que este caracol es un competidor fuerte y disminuye cultivos o plantas nativas por la polifagia.…”
Section: Introductionunclassified